Effect of spray drying conditions on the physicochemical, thermal, and microstructural properties of coffee mucilage powder (Coffea arabica–Castillo) - Rivera Escobar, Juan David; Hoyos Concha, Jose Luis; Roa-Acosta, Diego Fernando; Delgado, Jhan Carlos; Rosero-Benavides, Victor Hugo; Torres, Gerardo Andres (Frontiers in Sustainable Food Systems, 2025)
IntroductionCoffee mucilage is an abundant by-product generated during wet coffee processing, with potential applications as a natural ingredient due to its bioactive compounds. However, its high moisture content and intrinsic instability require technological processes such as spray drying (SD) to obtain a stable powdered ingredient. This study aimed to evaluate the effect of different SD operational conditions on the physicochemical, thermal, and microstructural properties of Coffea arabica L. cv. ‘Castillo’ mucilage powder.MethodsCoffee mucilage was obtained through enzymatic hydrolysis using commercial pectinases to facilitate polysaccharide breakdown. A mixed factorial approach was initially used to define hydrolysis conditions, followed by a central composite rotatable design that evaluated two SD factors: inlet air temperature (115.85–144.14 °C) and feed flow rate (0.23–0.66 L/h). Response variables included total phenolic content, antioxidant capacity (FRAP, ABTS, DPPH), glass transition temperature (Tg), particle size and morphology (SEM), zeta potential (PZ), hydrodynamic particle diameter (HPD), and sorption isotherms (BET and GAB).ResultsSD conditions significantly influenced the retention of phenolic compounds and antioxidant activity, with higher inlet temperature promoting increased bioactive concentration compared to feed flow rate. Phenolic content ranged from 135.53 to 165.88 mg GAE/100 g. CMP exhibited Tg values between 61.09 and 62.18 °C, with no significant inter-treatment effect. SEM images revealed predominantly spherical microparticles with corrugated surfaces, ranging from 14.93 to 22.03 μm2. where lower feed flow produced smaller particle size. Sorption isotherms indicated high hygroscopic behavior, and temperature significantly affected the monolayer moisture content (Xm) and sorption energy (C).Discussion/ConclusionTemperature was the most influential SD factor for the preservation of phenolic compounds and antioxidant capacity, while feed flow primarily impacted particle size. These findings provide technological insights for optimizing SD of coffee mucilage while preserving bioactive functionality and microparticle integrity, supporting its potential use in food formulations and the valorization of coffee by-products.